A queue model to monitor the conversion from ICEV to EV, HEV and DV in a scarce oil environment - Ferreira, M. A. M.; Filipe, J. A. (18th Conference on Applied Mathematics APLIMAT 2019 Proceedings, 2019)
Grounded on the M|G|∞ queue system, we build a model to analyze a situation in which ICEV-Internal Combustion Engine Vehicles, moved only by the action of an internal combustion engine, get idle, in a scarce conventional energy ambience, and are either recycled, turning either EV-Electric Vehicles or HEV-Hybrid Electric Vehicles, or dismantled becoming DV-Dismantled Vehicles. We model the three situations: EV, HEV and DV with the same purpose. The model allows concluding that when the rhythm ICEV become EV, HEV and DV is greater than the rate at which they become idle the system has a tendency to balance. In addition, we perform a cost-benefit analysis.